Development of a Red recombinase system and antisense RNA technology in Klebsiella pneumoniae for the production of chemicals. Issue 83 (23rd August 2016) - Li, Ying; Li, Sha; Ge, Xizhen; Tian, Pingfang
Abstract : Red recombinase system and antisense RNA technology were developed in Klebsiella pneumoniae . Abstract : Klebsiella pneumoniae is a promising industrial species, however the lack of genetic engineering tools restricts its applications. Here we developed a lambda (λ) Red recombinase system and antisense RNA technology in K. pneumoniae to reshape glycerol metabolism pathways. We deleted the lactate dehydrogenase gene ldh through RecA-dependent recombination to block lactic acid synthesis. Next, the 1, 3-propanediol dehydrogenase gene dhaT was replaced by an aldehyde dehydrogenase gene ( aldH from E. coli ) to repress 1, 3-propanediol (1, 3-PDO) synthesis and simultaneously convert 3-hydroxypropionaldehyde (3-HPA) to 3-hydroxypropionic acid (3-HP). Specially, we developed a Red recombinase system in K. pneumoniae, by which the enzymes related to glycerol metabolism were mutated by transformed oligos. One positive strain produced 6.39 g L −1 3-HP and 32.6 g L −1 1, 3-PDO at 36 h without using any antibiotics and inducers. Sequencing results showed that the mutation occurred mainly in byproduct pathways. Finally, antisense RNA technique was applied to block the synthesis of lactic acid and acetic acid. We found that the increase of 3-HP was approximately proportional to the decrease of lactic acid and acetic acid, indicating their competition for glycerol carbon flux. Overall these results and approaches developed in this study provide basis for basic research and microbial production of 3-HP, 1, 3-PDO and 2, 3-butanediol in K. pneumoniae .